APOA-1Milano muteins, orally delivered via genetically modified rice, show anti-atherogenic and anti-inflammatory properties in vitro and in Apoe−/− atherosclerotic mice. (15th November 2018) - Romano, Gabriele; Reggi, Serena; Kutryb-Zajac, Barbara; Facoetti, Amanda; Chisci, Elisa; Pettinato, Mariateresa; Giuffrè, Maria Rita; Vecchio, Federica; Leoni, Silvia; De Giorgi, Marco; Avezza, Federica; Cadamuro, Massimiliano; et al.
Abstract: Background: Atherosclerosis is a slowly progressing, chronic multifactorial disease characterized by the accumulation of lipids, inflammatory cells, and fibrous tissue that drives to the formation of asymmetric focal thickenings in the tunica intima of large and mid-sized arteries. Despite the high therapeutic potential of ApoA-1 proteins, the purification and delivery into the disordered organisms of these drugs is still limited by low efficiency in these processes. Methods and results: We report here a novel production and delivery system of anti-atherogenic APOA-1Milano muteins (APOA-1M) by means of genetically modified rice plants. APOA-1M, delivered as protein extracts from transgenic rice seeds, significantly reduced macrophage activation and foam cell formation in vitro in oxLDL-loaded THP-1 model. The APOA-1M delivery method and therapeutic efficacy was tested in healthy mice and in Apoe −/− mice fed with high cholesterol diet (Western Diet, WD). APOA-1M rice milk significantly reduced atherosclerotic plaque size and lipids composition in aortic sinus and aortic arch of WD-fed Apoe −/− mice as compared to wild type rice milk-treated, WD-fed Apoe −/− mice. APOA-1M rice milk also significantly reduced macrophage number in liver of WD-fed Apoe −/− mice as compared to WT rice milk treated mice. Translational impact: The delivery of therapeutic APOA-1M full length proteins via oral administration of rice seeds protein extracts (the 'rice milk') to the disordered organism, without any need of purification, might overcome the main APOA1-based therapies' limitations and improve the use of this molecules as therapeutic agents for cardiovascular patients. Highlights: A novel production and delivery system, via oral administration, of anti-atherogenic APOA-1Milano muteins (APOA-1M) APOA-1M muteins expressed in rice seeds retained anti-atherogenic and anti-inflammatory properties in vitro and in vivo Orally delivered full length APOA-1M proteins are athero-protective even if the organism is still exposed to high fat diet